Handling Victims of Sexual Violence Against Children - Syukriani, Rezi; Suryadi, Suryadi; Mulia, Rizki Afri; Syamsir, Syamsir (Adabi : Journal of Public Administration and Business, 2023)
This research aims to find out how victims of sexual violence against children are handled at the Population Control Service, Family Planning, Women's Empowerment, and Child Protection, Agam Regency, and to find out what obstacles are faced and the efforts made. This research uses a qualitative descriptive method with a purposive sampling technique. Collecting research data from literature studies and field studies (interviews and observations). The research results show that the simplest step in handling cases of sexual violence against children is the family. Apart from that, the handling of victims of sexual violence against children at the Population Control Service, Family Planning, Women's Empowerment, and Child Protection, Agam Regency, is carried out in three ways, namely restitution, compensation, and rehabilitation. The obstacle that occurs in handling victims of sexual violence against children at the Population Control Service, Family Planning, Women's Empowerment, and Child Protection, Agam Regency, is the lack of understanding of victims or the community in understanding the behavior of children who are victims of sexual violence. Efforts made to deal with obstacles that occur in handling victims of sexual violence against children include socializing and providing counseling on how to handle acts of sexual violence against children in the family and community.